(3JdbjM GdYbhd (B((3aj GdCeKGd hGdMce(B)s - (3HQjI Hf CHj GdjSQ GdQjGVjs
(3ChdgG (B:s
(3GdMeO ddg GdPi GfYe Ydi GdEfSGf ef Hjf LejY GdMjhGf HaVjdI GdHjGf cGf YHO CejQ GdeDefjf , CYdi Gddg PcQg , Cda cJGHG ai GdCeKGd GdSGFQI GfJgi ajg Edi ebOGQ GdWGbI ai Pdc GdhbJ ,adeG SGaQ YHO CejQ GdeDefjf Edi GdYQGb s
(3BNQgG (B:s
(3ehba GdHjf MLQ GdThb ai cHOi Xei GdMTG hOhYi JLQgf XeG s
(3JedcgG eMeO bfGhi heMeO GHf eMeO GdgQjOi GdMdHi de jPcQ cTa GdXfhf GSe eDda GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdLRA (B1 - (3U (B481 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B205 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs